Unpacking the Pay Satisfaction Paradox: The Interplay of Work Pressure and Life Balance in Predicting Employee Turnover within Urban Hospitality - Sophia Widya Kirana; Budi Prabowo (FEBI IAIN Langsa, 2026)
High employee turnover (12% in 2023) at Fave Hotel Rungkut Surabaya necessitates a rigorous investigation into retention determinants. This study analyzes the influence of work pressure, pay satisfaction, and work life balance on turnover intention through the lens of Social Exchange Theory. Employing a quantitative explanatory research approach, data were collected from a census of 50 employees using a 4-point forced choice Likert scale. Multiple linear regression analysis reveals that these factors simultaneously explain 66.7% of the variance in turnover intention ( = 0.667). Partially, work pressure emerged as the most dominant positive driver of exit intentions. Notably, the study identifies a